Contaminants migrating from crossed-linked polyethylene pipes and their effect on drinking water odour. (15th September 2019) - Kalweit, Cynthia; Stottmeister, Ernst; Rapp, Thomas
Abstract: The formation potential of contaminants diffusing from cross-linked polyethylene (PE-X) pipes and their impact on the odour of drinking water was determined. Three types of PE-X material, Pe-Xa, PE-Xb and PE-Xc, were extensively assessed by performing migration tests following EN 1420 and EN 12873–1. Migration waters were analysed for their threshold odour number (TON). The same samples were investigated by two gas chromatography-mass spectrometry methods: screening and olfactometry. Most of the PE-X materials failed the German regulation of TON <2 for cold water and TON ≤4 for warm water. PE-Xb material caused the strongest odour and also released the highest amount of contaminants. Metilox, 7, 9-di-tert-butyl-1-oxaspiro(4, 5)deca-6, 9-diene-2, 8-dione, 3, 5-di-tert-butyl-4-hydroxybenzaldehyde and 2, 6-di-tert-butyl-p-benzoquinone (2, 6-DtBQ) were the most often detected substances leaching from the tested plastic materials. However, no odour was perceived for most of these substances. Methyl tert-butyl ether (MtBE) and 2-tert-butylphenol are believed to contribute to the sensory problem in the migration water among other substances such as tert-amyl methyl ether, 2, 2, 2, 5-tetramethyltetrahydrofuran, toluene or xylene. In total ten specific descriptions characterized the odour of the individual contaminants: ethereal, fresh, solvent, sweet, fruity, floral, unsavoury, pungent, aromatic and chemical. Graphical abstract: Image 1 Highlights: Polyethylene pipes release contaminant in drinking water. These can be responsible for off-flavour. Most of the investigated pipes failed the German requirements. Ten specific odours characterised individual contaminants. No odour was perceived for many of the identified substances.